1982
DOI: 10.4315/0362-028x-45.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and Control of Bacterial Spore Germination

Abstract: Factors affecting germination of bacterial spores as well as chemical inhibition of germination are reviewed. Current theories on the nature of initiation of the germination process are also presented. Transformation of a dormant bacterial spore into a metabolically active vegetative cell involves a myriad of complex biochemical events of which the “trigger reaction” is thought to be the prime event. The ability to control or prevent this complex sequence of events from occurring by manipulation of environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 0 publications
0
22
0
1
Order By: Relevance
“…The effects of inhibitors of germination have been widely reported, but it is often not known at what stage of germination an inhibitor is active (193). Because of the nature of the germination process, the only types of antibacterial agents that are effective are those that inhibit the trigger reaction and those that prevent the degradative processes.…”
Section: Germinationmentioning
confidence: 99%
See 3 more Smart Citations
“…The effects of inhibitors of germination have been widely reported, but it is often not known at what stage of germination an inhibitor is active (193). Because of the nature of the germination process, the only types of antibacterial agents that are effective are those that inhibit the trigger reaction and those that prevent the degradative processes.…”
Section: Germinationmentioning
confidence: 99%
“…Because of the nature of the germination process, the only types of antibacterial agents that are effective are those that inhibit the trigger reaction and those that prevent the degradative processes. (193). Thus, whereas many compounds are likely to prevent the degradative processes, it is unclear whether the trigger reaction is also affected.…”
Section: Germinationmentioning
confidence: 99%
See 2 more Smart Citations
“…when compared with an atmosphere of 100% N 2 . However, Smoot and Pierson (1982) reported that CO 2 had little effect on germination and toxigenesis of spore formers such as Clostridium botulinum. Of the microbial associations developed in pizza samples under aerobic and modified atmospheric storage, yeast/molds were found to be a member, and along with LAB, psychrotrophs and to lesser extent coliforms, play a significant role in spoilage of baked pizza.…”
Section: Resultsmentioning
confidence: 99%